SATU ABAD NAHDHATUL ULAMA BERKIPRAH: RESPONSI PARA KYAI PESANTREN MENGHADAPI PERUBAHAN SOSIAL POLITIK DAN KEAGAMAAN AWAL ABAD KEDUAPULUH - Riyadh Firdaus, Muhamad; Hunainah, Hunainah (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
This research aims to examine the response of Islamic boarding school kyai in facing the social changes that are occurring, especially in the political and religious aspects. It is always interesting to study Kyai and their role and really analyze them. kiyai is a good character. By his words and deeds, he acts as a guide for people. Kyai is inseparable from his knowledge of religion, so people always talk to him about religious matters. There has been a polarization of kiyai views lately. Kyai must play the role of protector in religious life, so in order not to be trapped in a dual role, it is better for kiyai to avoid political activities. But there's no reason to feel that way. Abandon political activism because it is part of the religion of life. When Kyai chose politics, his relationship with society began to fade. This is the antithesis, politics is full of hustle and bustle, but religious people are full of loyalty.